Pengaruh Penerbitan Sukuk Ijarah dan Ukuran Perusahaan Terhadap Profitabilitas Perusahaan yang Menerbitkan Sukuk Ijarah di Bursa Efek Indonesia Tahun 2017-2020 - Agnesti, Agnesti (BISMA : Business and Management Journal, 2023)
Company profitability can be interpreted as a prospect or future, many factors can affect the level of profitability of a company, so that companies are required to make efforts to obtain the maximum profit. One indicator of company profitability can be seen from the return on equity of the company itself. Factors that can affect a company's profitability include the company's ability in capital structure policies and how the company uses its assets. Based on the background above, this research was conducted to test and study the effect of the ratio of sukuk to equity and company size on the profitability of companies listed on the IDX for the 2017-2020 period. Source of data in this research comes from secondary data. The data analysis method used is quantitative, namely using multiple linear regression analysis and using Microsoft Excel 2010 and Eviews 10 computer program tools. The data is obtained from the annual financial reports of companies that issue sukuk ijarah for the 2017-2020 period. The results of this study indicate that the probability value of issuing sukuk ijarah is 0.2806 > 0.05 so that sukuk ijarah has no significant effect on profitability and firm size has a significant effect on company profitability with a probability value of 0.0483 <0.05. And simultaneously the independent variables affect the dependent variable with a probability value of 0.027329 <0.05.